KEARIFAN LOKAL MENGONGKO PETANI PALA DI DESA BUMBIHA KECAMATAN SIAU BARAT KABUPATEN KEPULAUAN SIAU TAGULANDANG BIARO - Theophilus A. Sitohang (Universitas Sam Ratulangi, 2023)
The Indonesian state has a diversity of ethnic groups, cultures, customs, languages, geographical locations, different natural conditions that give birth to humans who live side by side and are able to adapt to natural conditions in supporting survival. This diversity is a social potential that is an important part of the formation of cultural image and identity Traditional cultivation is a system that has been passed down from generation to generation so that it becomes the local knowledge of farmers. This local knowledge system provides an overview of the wisdom of community traditions in utilizing natural and social resources wisely which refers to environmental balance and sustainability. Nutmeg farming on Siau Island is a very good and profitable nutmeg farming for nutmeg farmers because of the fertile soil with the Karangetang Volcano. The people of Siau Island have a culture, traditions, and customs that still prevail today, namely Mengongko. Mengongko tradition is the activity of picking up nutmeg that has fallen to the ground. If nutmeg seeds that have fallen on the ground belong entirely to everyone if they find them, except taking nutmeg on the tree directly, it is prohibited by the customs on Siau Island. The local wisdom of nutmeg farmers in Bumbiha Village is still very thick before harvest: cleaning (menibase), controlling (mengenang) and informing (menguli); harvest period: climbing (mengawi), helping to split (mesumbala memeka), drying (mematih), and selling (mebalu). Keywords: local wisdom, nutmeg farmer, mengongko